FORMATION OF ENVIRONMENTAL COMPETENCE OF FUTURE TEACHERS AS A COMPONENT OF THEIR PROFESSIONAL COMPETENCE - Valentina А. Fritsyuk; Natalia V. Bayurko; Vasyl M. Fritsyuk (Alfred Nobel University Publisher, 2022)
The article deals with the issue of preparation of future teachers to the development of ecological competence of secondary school pupils. A key figure in the formation of ecological competence of future generations of citizens is the teacher. Hence, professional qualifications of students working for a university degree in the field of teaching, their environmental education, environmental literacy, readiness for carrying out nature protection activities with children as well as their civic stance are crucial for the professional training of teachers. The authors analyse theoretical principles of the investigated problem, determine the essence of ecological competence, «readiness of future teachers of biology to the development of ecological competence of secondary school pupils», as an integrative characteristic of personality that shows in the attitude of students to the development of pupils' ecological competence, students' the realization of reasons and requirements in this activity. This is also demonstrated in the existence of thorough and versatile subject knowledge of disciplines in the chosen profession and ecological, psychological and pedagogical, social and ecological, methodological knowledge, abilities and skills in relation to the development of ecological competence of junior adolescents. The study theoretically proved and experimentally tested pedagogical conditions and methods of forming readiness of future teachers to the development of ecological competence of secondary school pupils in the process of learning at higher educational pedagogical establishments: activation of the need of students in capturing the methods of developing ecological competence of schoolchildren; using at the lessons in professional disciplines the design of fragments of professional and pedagogical activity for providing personal implication of students in ecological and educational activity; the motivated usage of tasks of ecological orientation in different types of practices undertaken by future biology teachers.